Hubungan Tingkat Pengetahuan tentang Hipertensi dengan Dukungan Keluarga pada Penderita Hipertensi Usia Lanjut di Pungkuran Pleret Bantul - Riza Yulina Amry (STIKes Surya Global Yogyakarta, 2020)
Background: Hypertension is a non-communicable disease that is often found in people with blood pressure more than 140/90 mmHg. Family support is very important for the elderly to control the disease. Objective: This study aimed to determine whether there was a relationship between knowledge with family support in the care of elderly sufferers with hypertension.Methods: Cross sectional is the research design chosen in this study. The population in this study are families who have elderly with hypertension, the sampling technique used total sampling with a total sample of 52 elderly families with hypertension. The method of data analysis used the Spearman Rank test with delete Microsoft Excel and IBM SPSS Statistics 20.Results: There was a relationship between the level of family knowledge about hypertension and the provision of family support in elderly hypertensive patients with a p value = 0.017. Support was divided into 3 categories, namely emotional support and appreciation with a value of p = 0.367, information support 0.003 and the last was instrumental support with a value of p = 0.783. In total the level of knowledge affects the family in providing support to the elderly with hypertension. Three types of support that have knowledge only affect family support in providing information.Conclusion: The level of knowledge about hypertension affecting families in providing support is primarily information support.Keywords: knowledge, hypertension, family support